2012
DOI: 10.1179/1024529412z.00000000019
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Alternative Start-Up Business Funding

Abstract: The broad context for our study is set by discussions of equality of opportunity to start-up business finance. There is an increasing literature which suggests that female entrepreneurs face significant disadvantages compared to their male counterparts in their access to resources from orthodox channels such as banks. The consequence of undercapitalization during the start-up phase is underperformance during the life of the business. Adopting a range of informal 'bootstrapping' techniques gives entrepreneurs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…However, considering minimisation of investments, females have a higher mean than males. The results are consistent with the findings of Jayawarna et al (2012). The study found gender differences in some of the measures of financial bootstrapping.…”
Section: Need For External Financesupporting
confidence: 91%
“…However, considering minimisation of investments, females have a higher mean than males. The results are consistent with the findings of Jayawarna et al (2012). The study found gender differences in some of the measures of financial bootstrapping.…”
Section: Need For External Financesupporting
confidence: 91%
“…Research in this tradition has focused on the difficulty female entrepreneurs have in accessing capital (Carter et al, 2003) or the fact that males and females tend to have very different social networks (Jones and Jayawarna, 2010). In the latter case, female networks are typically dominated by strong ties (family and friends) with limited links to more professional networks which provide access to a wider range of resources (Jayawarna et al, 2012). From a more theoretical perspective, there is a clear difference between those who subscribe to the idea that 'alert' entrepreneurs are able to identify new opportunities which have an objective reality (Shane, 2003;Shane and Venkataraman, 2000) and the opposing view that opportunities are created (Sarasvathy, 2001) rather than discovered.…”
Section: Dualisms In Entrepreneurship Researchmentioning
confidence: 98%
“…Women face more obstacles in getting external finance in general as a result of gender stereotyping (Jayawarna et al, 2012;Marlow & Patton, 2005). For instance, Fay and Williams (1991) suggest that approvals for start-up loans for women are significantly lower than for their male counterparts.…”
Section: Access To External Financementioning
confidence: 99%